Analisis Yurisdiksi Negara dalam Hukum Pidana Internasional terhadap Kejahatan Genosida - Rizki Prasetio; Mochamad Farhan Agung; Hermalia Putri (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The term genocide consists of two words, namely geno and cide. Genoa or genos comes from Ancient Greek which means race, nation or ethnicity. Meanwhile, cide, caedere, or cidium comes from Latin which means to kill. Literally, genocide can mean the killing of a race. This term was introduced by Raphael Lemkin in 1944, a Polish-born Jew who immigrated to America in 1930 in his book Axis Rule In Occupied Europe. So it can be interpreted that genocide is a large-scale, systematic massacre of an ethnic group or a group of ethnic groups with the intention of exterminating them. Genocide is defined as any act committed to destroy, in whole or in part, a national, ethnic, racial, or religious group, including killing members of the group, causing serious physical or mental injury to members of the group, and other acts to bring about its destruction. physical group. We need to know that after knowing the definition of genocide, we need to study the meaning of a State's jurisdiction in international law regarding the crime of genocide. The word jurisdiction (jurisdiction) comes from the word jurisdictio which comes from two words, namely juris and dicio. Juris means legal ownership or legal ownership. As for dictio, it means speech, statement, or title. Thus, judging from the origin of the word, it appears that jurisdiction is related to legal matters, ownership according to law or authority according to law. So, as we have learned, there are efforts by a State or nation to have authority according to international criminal law as concrete efforts to take responsibility for a State in preventing the crime of genocide. For example, in the case of genocide, there have been crimes committed by the Myanmar government against the Rohingya Muslim ethnic group, because they fulfilled several basic elements, namely mass murder, discrimination against religious minorities, carried out systematically, and aimed at eliminating a particular ethnicity and group.